Applying thieno[3, 2-b]thiophene as a building block in the design of rigid extended thienoacenes. Issue 99 (12th October 2016) - Magnan, François; Gabidullin, Bulat; Brusso, Jaclyn L.
Abstract : The synthesis of rigid extended star-shaped thienoacenes that incorporate thieno[3, 2- b ]thiophene as a structural unit, either as the "core" or "arm" moiety, is described herein. Abstract : The synthesis of rigid extended star-shaped thienoacenes that incorporate thieno[3, 2- b ]thiophene as a structural unit, either as the "core" or "arm" moiety, is described herein. Four-fold Negishi coupling of a tetrabrominated core with thienyl- or thienothienyl zincates, followed by oxidative cyclodehydrogenation, affords tetra(5-hexyl)thieno([3, 2- b ]thieno)anthracene, tetra(5-hexylthieno[3, 2- b ]thieno)acridine, tetra(5-hexylthieno)benzothieno[3, 2- b ]benzothiophene and tetra(5-hexylthieno[3, 2- b ]thieno)benzothieno[3, 2- b ]benzothiophene. Comparative electrochemical, optical, computational and single crystal X-ray diffraction studies were carried out on this family of star-shaped thieno[3, 2- b ]thiophene based molecules to demonstrate, and confirm, the conservation of rigidity upon extending the conjugation, as well as to investigate the influence of the substitution pattern and heteroatom incorporation on the optoelectronic and solid state properties.